1970
DOI: 10.1017/s0022377800004979
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron harmonic wave propagation and instabilities: I. Perpendicular propagation

Abstract: Parts I and II of this paper present a comprehensive picture of longitudinal wave propagation in a warm homogeneous magnetoplasma. Part I discusses computed dispersion characteristics for propagation perpendicular to the static magnetic field. For a ring electron velocity distribution it is found that mode coupling and absolute instability can occur. Similar effects are predicted for a spherical shell distribution. The Maxwellian distribution gives rise to stable propagation of undamped waves, and attenuating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(65 citation statements)
references
References 7 publications
6
59
0
Order By: Relevance
“…The Debye length can be deduced from F pe /F ce and r L , λ D = r L F ce /F pe = 3.8 m, which has to be compared to the 80 m of the Viking spherical double probe length. The wavelengths of the Bernstein's resonances F q2 , F q3 , and F q4 can also be calculated; they are equal to 32 m, 17 m, and > 9 m (see F qn dispersion diagram in Tataronis and Crawford, 1970), respectively. Although these wavelengths are shorter than the antenna length, they were clearly seen by the Viking sounder (Perraut et al, 1990).…”
Section: Plasma Resonances Observed By Whispermentioning
confidence: 99%
“…The Debye length can be deduced from F pe /F ce and r L , λ D = r L F ce /F pe = 3.8 m, which has to be compared to the 80 m of the Viking spherical double probe length. The wavelengths of the Bernstein's resonances F q2 , F q3 , and F q4 can also be calculated; they are equal to 32 m, 17 m, and > 9 m (see F qn dispersion diagram in Tataronis and Crawford, 1970), respectively. Although these wavelengths are shorter than the antenna length, they were clearly seen by the Viking sounder (Perraut et al, 1990).…”
Section: Plasma Resonances Observed By Whispermentioning
confidence: 99%
“…Since ANx is undulatory about zero, unstable solutions are anticipated (Tataronis and Crawford, 1970). In Appendix A It is shown that in uslnq a threetern approximation to equation ( '/iz1.8 0…”
Section: A the Bernstein Modementioning
confidence: 99%
“…The solutions are equivalent to those obtained by Tataronis and Crawford (1970) using the electrostatic approximation to the dispersion relation. …”
Section: 1(1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tataronis and Crawford (1970) have recently given a survey of these instabilities found by Harris (1959) supposing different anisotropic velocity distributions of electrons. Branches of the dispersion curves with negative group velocity exist in all these cases not only near the hybrid frequency but also near the gyroharmonics in a fashion similar to Figure 3a.…”
Section: Remarks On Type Iv#-burstsmentioning
confidence: 99%